CFD Simulation of NACA 2412 airfoil with new cavity shapes - Samuel, Merryisha; Rajendran, Parvathy; Khan, Sher Afghan (Techno Press, 2022)
The paper presents the surface-modified NACA 2412 airfoil performance with variable cavity characteristics such as size, shape, and orientation, by numerically investigated with the pre-validation study. The study attempts to improve the airfoil aerodynamic performance at 30 m/s with a variable angle of attack (AOA) ranging from 0° to 20° under Reynolds number (Re) 4.4×105. Through passive surface control techniques, a boundary layer control strategy has been enhanced to improve flow performance. An intense background survey has been carried out over the modifier orientation, shape, and numbers to differentiate the sub-critical and post-critical flow regimes. The wall-bounded flows along with its governing equations are investigated using Reynolds Average Navier Stokes (RANS) solver coupled with one-equational transport Spalart Allmaras model. It was observed that the aerodynamic efficiency of cavity airfoil had been improved by enhancing maximum lift to drag ratio ((l/d) max) with delayed flow separation by keeping the flow attached beyond 0.25C even at a higher angle of attack. Detailed investigation on the cavity distribution pattern reveals that cavity depth and width are essential in degrading the early flow separation characteristics. In this study, overall general performance comparison, all the cavity airfoil models have delayed stalling compared to the original airfoil